The Sustainable Criteria In Supplier Selection: A Review - Wan Mahmood, Wan Hasrulnizzam; Tukimin, Rahayu; Mohd Razali, Muhamad; Yusup, Mohd Zaki (Publications International Lahore, Pakistan, 2014)
Supplier selection has received great attention recently since the cost of raw material constitutes the main cost of product. Choosing the best supplier provides the best quality of materials, on time, at the right price, and the right level of service. Due to globalization in business, competitive market situations and the changing customers’ demands nowadays, organizations should add environmental and social aspects to the existing supplier selection criteria to remain sustainable in supply chain. Reviewing the literature and considering the developed framework for sustainable supplier selection, this paper aims at presenting the sustainable supplier selection criteria and discussed the interdependency between the criteria presented.